RESULTS OF ANALYSIS OF BENCHMARKING METHODS OF INNOVATION SYSTEMS ASSESSMENT IN ACCORDANCE WITH AIMS OF SUSTAINABLE DEVELOPMENT OF SOCIETY - A. Vylegzhanina (Модернизация, инновация, развитие, 2016)
In this work, we introduce results of comparative analysis of international ratings indexes of innovation systems for their compliance with purposes of sustainable development. Purpose of this research is defining requirements to benchmarking methods of assessing national or regional innovation systems and compare them basing on assumption, that innovation system is aligned with sustainable development concept. Analysis of goal sets and concepts, which underlie observed international composite innovation indexes, comparison of their metrics and calculation techniques, allowed us to reveal opportunities and limitations of using these methods in frames of sustainable development concept. We formulated targets of innovation development on the base of innovation priorities of sustainable socio-economic development. Using comparative analysis of indexes with these targets, we revealed two methods of assessing innovation systems, maximally connected with goals of sustainable development. Nevertheless, today no any benchmarking method, which meets need of innovation systems assessing in compliance with sustainable development concept to a sufficient extent. We suggested practical directions of developing methods, assessing innovation systems in compliance with goals of societal sustainable development.